Identification of the secreted watery saliva proteins of the rice brown planthopper, Nilaparvata lugens (Stål) by transcriptome and Shotgun LC–MS/MS approach. (June 2016) - Liu, Xiaoqing; Zhou, Hanyu; Zhao, Jing; Hua, Hongxia; He, Yueping
Graphical abstract: Highlights: Watery saliva proteins of rice brown planthoppers were identified by transcriptome and gel-free LC–MS/MS. In total 107 proteins were identified in the saliva. Including 29 proteins with catalytic activity and 24 proteins with binding activity. Abstract: The rice brown planthopper, Nilaparvata lugens (Stål), a major rice insect pest in Asia, is a vascular bundle-feeder that ejects gelling and watery saliva during the feeding process. Although major proteins in the salivary glands of N. lugens have been identified using 2D PAGE, very little is known about the secreted saliva of this insect. In this study, we identified the major proteins in the secreted watery saliva of N. lugens, via collecting from a sucrose diet that adult planthoppers had fed upon through a membrane of stretched parafilm, and using shotgun LC–MS/MS analysis with reference to transcriptome database of salivary glands of N. lugens . A total of 107 proteins were identified in the watery saliva of N. lugens, over 80% of which showed significant similarity to known proteins. When annotated by the Blast2GO suite, 29 proteins had catalytic activity and 24 proteins were binding proteins. The saliva enzymes included oxidoreductases, hydrolases, phosphatases, peptidases (proteases), kinases, transferases, and lyases. Binding proteins in N. lugens watery saliva included ATP-binding, lipophorin, calcium-binding, actin-binding and DNA-, RNA-, and chromatin-binding proteins. Other non-enzymatic proteins, such as ubiquitins, heat shock proteins, ribosomal proteins, and immunoglobulin proteins were also found in N. lugens watery saliva. This is the first study to identify, characterize and list the proteins in watery saliva of N. lugens, which might be involved in planthopper–rice interactions.